The Fujimori legacy : the rise of electoral authoritarianism in Peru - Carrión, Julio F. Hrsg (Pennsylvania State University Press, 2006)
The rise and decline of Fujimori's neopopulist leadership / Kurt Weyland -- An authoritarian presidency : How and why did presidential power run amok in Fujimori's Peru? / Philip Mauceri -- Fujimori and the mayors of Lima, 1990-2001 : the impact and legacy of neopopulist rule / Robert R. Barr and Henry Dietz -- Do parties matter? : lessons from the Fujimori experience / Kenneth M. Roberts -- The immoral economy of Fujimorism / Catherine M. Conaghan -- Public opinion, market reforms, and democracy in Fujimori's Peru / Julio F. Carrión -- All the president's women : Fujimori and gender equity in Peruvian politics / Gregory D. Schmidt -- Redirection of Peruvian economic strategy in the 1990s : gains, losses, and clues for the future / John Sheahan -- Against the odds : the paradoxes of Peru's economic recovery in the 1990s / Carol Wise -- The often surprising outcomes of asymmetry in international affairs : United States-Peru relations in the 1990s / David Scott Palmer -- Electoral authoritarian versus partially democratic regimes : the case of the Fujimori government and the 2000 elections / Cynthia McClintock -- Endogenous regime breakdown : the Vladivideo and the fall of Peru's Fujimori / Maxwell A. Cameron -- The rise and fall of electoral authoritarianism in Peru / Julio F. Carrión